2019
DOI: 10.1159/000503439
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Care Gaps in Home Dialysis: The Home Dialysis Virtual Ward Study

Abstract: Background: Home dialysis patients may be at an increased risk of adverse events after transitional states. The home dialysis virtual ward (HDVW) trial was conducted in Canadian dialysis centers and aimed to evaluate potential care gaps and patient satisfaction during the HDVW. Methods: The HDVW was a multicenter single-arm trial including peritoneal dialysis and home hemodialysis patients after 4 different events (hospital discharge, medical procedure, antibiotics, completion of training). Telephone-led inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 43 publications
0
9
0
1
Order By: Relevance
“…Furthermore, 34 quantitative studies were considered for assessment (see Table S3). From the excluded 12 studies, ten 35–44 were not fully accessible and one study was based on simulation 45 and one on component analysis 46 . The four mix‐method studies 47–50 were assessed based on both qualitative and quantitative criteria.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, 34 quantitative studies were considered for assessment (see Table S3). From the excluded 12 studies, ten 35–44 were not fully accessible and one study was based on simulation 45 and one on component analysis 46 . The four mix‐method studies 47–50 were assessed based on both qualitative and quantitative criteria.…”
Section: Resultsmentioning
confidence: 99%
“…Examples of a reduced program ask could include the following: reduced frequency of blood work, outsourcing the dialysate and water sampling to technicians, reducing the number of in-person clinic visits in favor of virtual medicine, and reducing the frequency of audit requirements. Regular bi-annual vascular access audits in conjunction with re-training for patients at risk are important interventions that can reduce patient error 26,27 and hopefully lead to a decrease in technique failure.…”
Section: Discussionmentioning
confidence: 99%
“…The HDVW study also found that potential gaps in care were frequently encountered after transitional events in home dialysis patients, such as after start of home dialysis. 20 Such follow-up tools might help to reduce fear of isolation, a frequently named limitation for HHD 21 while minimizing the likelihood of adverse events. To reduce the need for home follow-up visits, simulation initiatives have also been studied.…”
Section: Discussionmentioning
confidence: 99%